Chemical and biosynthetic potential of Penicillium shentong XL-F41 - Zou, Ran; Li, Xin; Chen, Xiaochen; Guo, Yue-Wei; Xu, Baofu (Beilstein Journal of Organic Chemistry, 2024)
Penicillium strains are renowned for producing diverse secondary metabolites with unique structures and promising bioactivities. Our chemical investigations, accompanied by fermentation media optimization, of a newly isolated fungus, Penicillium shentong XL-F41, led to the isolation of twelve compounds. Among these are two novel indole terpene alkaloids, shentonins A and B (1 and 2), and a new fatty acid 3. Shentonin A (1) is distinguished by an unusual methyl modification at the oxygen atom of the typical succinimide ring, a feature not seen in the structurally similar brocaeloid D. Additionally, shentonin A (1) exhibits a cis relationship between H-3 and H-4, as opposed to the trans configuration in brocaeloid D, suggesting a divergent enzymatic ring-expansion process in their respective fungi. Both shentonins A (1) and B (2) also feature a reduction of a carbonyl to a hydroxy group within the succinimide ring. All isolated compounds were subjected to antimicrobial evaluations, and compound 12 was found to have moderate inhibitory activity against Candia albicans. Moreover, genome sequencing of Penicillium shentong XL-F41 uncovered abundant silent biosynthetic gene clusters, indicating the need for future efforts to activate these clusters and unlock the full chemical potential of the fungus.
Keywords: genome analysis; indole terpene alkaloid; natural products; Penicillium; structure elucidation